Marquina, Antonio (ed.) (2010): Global Warming and Climate Change. Prospects and Policies in Asia and Europe, Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan - Tomé Alonso , Beatriz (UNISCI Discussion Papers, 2010)
Sin resumen